2016
DOI: 10.2166/nh.2016.020
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical classification of groundwater using multivariate statistical analysis in Latvia

Abstract: Multivariate statistical methodsprincipal component analysis (PCA) and hierarchical cluster analysis (HCA)are applied to identify geochemically distinct groundwater groups in the territory of Latvia. The main processes observed to be responsible for groundwater chemical composition are carbonate and gypsum dissolution, fresh and saltwater mixing and ion exchange. On the basis of major ion concentrations, eight clusters (C1-C8) are identified. C6 is interpreted as recharge water not in equilibrium with most sed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 26 publications
0
13
0
1
Order By: Relevance
“…In addition, dissolved or gaseous methane, sulfides, and hydrogen can be important indicators in subaqueous freshwater springs. Many studies have used springs geochemistry to describe karstic or deep‐aquifer springs sourcing (e.g., Shuster and White 1971, Huntoon 2000, Crossey et al 2009, Hershey et al 2010, Springer et al 2017), and multivariate statistical techniques have revealed spatial and anthropogenic impacts, including as seawater intrusion into coastal aquifers (e.g., Yidana 2010, Retike et al 2016). However, while essential to understanding springs aquifer sourcing, ecosystem ecology, and utility for human use, like other aquifer and groundwater metrics, springs geochemistry does not readily or unambiguously distinguish springs ecosystems and thus remains of secondary importance in classification.…”
Section: Springs Ecosystem Classification and Approachesmentioning
confidence: 99%
“…In addition, dissolved or gaseous methane, sulfides, and hydrogen can be important indicators in subaqueous freshwater springs. Many studies have used springs geochemistry to describe karstic or deep‐aquifer springs sourcing (e.g., Shuster and White 1971, Huntoon 2000, Crossey et al 2009, Hershey et al 2010, Springer et al 2017), and multivariate statistical techniques have revealed spatial and anthropogenic impacts, including as seawater intrusion into coastal aquifers (e.g., Yidana 2010, Retike et al 2016). However, while essential to understanding springs aquifer sourcing, ecosystem ecology, and utility for human use, like other aquifer and groundwater metrics, springs geochemistry does not readily or unambiguously distinguish springs ecosystems and thus remains of secondary importance in classification.…”
Section: Springs Ecosystem Classification and Approachesmentioning
confidence: 99%
“…Data preprocessing included: (1) removal of historical samples which reported sodium and potassium as a sum (NaK) (an additional criterion); (2) removal of samples with ionic balances error greater than ± 10% as suggested by Müller et al (2006) and 3where such information was available samples with nitrate content exceeding 4 mg/l were removed as potentially affected by human activities. Much stricter criterion than suggested 10 mg/l by Müller et al 2006 was chosen based on most recent study about geochemical composition of groundwater in Latvia (Retike et al 2016).…”
Section: Materials and Data Preprocessingmentioning
confidence: 99%
“…Much stricter criteria were used, and value of the inflection point for chloride was set 18 mg/l. Results were compared with values obtained by Retike et al (2016). Next, BL for chloride ion was determined as 90 th percentile of all freshwater samples below the inflection point value according to BRIDGE methodology (Müller et al 2006).…”
Section: Determination Of Background Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aptuveni pusē avotu ir pārsniegts pieļaujamais dzelzs, divos avotos sulfātjonu saturs, tomēr šo parametru pārsniegums nerada draudus cilvēka veselībai (Veselības inspekcija 2016). Divos avotos ir pārsniegta pieļaujamā amonija vai nitrātu koncentrācija, novērots, ka vismaz pusē paraugu ir pazemes ūdeņiem neraksturīgi augsta nitrātjonu vērtība (Retike et al 2016). Tas liecina, ka avota ūdens kopumā ir relatīvi vāji aizsargāts pret iespējamu virszemes piesārņojumu un tajā varētu būt pārsniegta arī līdz šim neanalizētu parametru pieļaujamā vērtība.…”
Section: Secinājumiunclassified